Ivan the Terrible in Russian historical memory since 1991 - Halperin, Charles J. (Studies in Russian and Slavic literatures, cultures and history., 2021)
"Tsar Ivan the Terrible (Ivan IV, 1533-1584) is one of the most controversial rulers in Russian history, infamous for his cruelty. He was the first Russian ruler to use mass terror as a political instrument, and the only Russian ruler to do so before Stalin. Comparisons of Ivan to Stalin only exacerbated the politicization of his image. Russians have never agreed on his role in Russian history, but his reign is too important to ignore. Since the abolition of censorship in 1991 professional historians and amateurs have grappled with this problem. Some authors have manipulated that image to serve political and cultural agendas. This book explores Russia's contradictory historical memory of Ivan in scholarly, pedagogical and political publications"--